2021
DOI: 10.1016/j.xinn.2021.100171
|View full text |Cite
|
Sign up to set email alerts
|

Urban-rural disparity of the short-term association of PM2.5 with mortality and its attributable burden

Abstract: PM 2.5 had greater effects on CVD/CED mortality in urban cities than rural areas -PM 2.5 had stronger effects on RESP mortality in rural areas than urban cities -An annual mean of 16.5/100,000 deaths was attributable to PM 2.5 in urban cities -An annual mean of 3.4//100,000 deaths was attributable to PM 2.5 in rural areas -Spatially targeted measures are needed to reduce PM 2.5 -related mortality in China ll www.cell.com/the-innovation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The green shaded region shows Ntyr concentrations derived from the extraction of bronchoalveolar lavage (BAL) fluid. , The pollutant concentrations are chosen based on measurements reported in the literature (Table S3). , …”
Section: Resultsmentioning
confidence: 99%
“…The green shaded region shows Ntyr concentrations derived from the extraction of bronchoalveolar lavage (BAL) fluid. , The pollutant concentrations are chosen based on measurements reported in the literature (Table S3). , …”
Section: Resultsmentioning
confidence: 99%
“…Many studies have examined health inequalities associated with air pollution, providing evidence that socio-economic deprivation could exacerbate the adverse health effects of air pollution (Castillo et al, 2021;T. Liu et al, 2021;Martins et al, 2004;Morelli et al, 2016;Wong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined health inequalities associated with air pollution, providing evidence that socio‐economic deprivation could exacerbate the adverse health effects of air pollution (Castillo et al., 2021; T. Liu et al., 2021; Martins et al., 2004; Morelli et al., 2016; Wong et al., 2008). Recently, a nationwide study including 2,640 Chinese counties found that people living in counties with lower literacy, college education, GDP per capita, and urbanization levels were more vulnerable to the mortality risks of long‐term PM 2.5 exposure than those living in counties with higher levels of these parameters (L. Han et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Fine particulate matter (PM 2.5 , particles with aerodynamic diameter less than 2.5 μm) pollution seriously threatens human health. Ultrafine particles (UFPs, particles with aerodynamic diameter less than 0.1 μm) are particularly important, as they may be able to translocate across the respiratory epithelium and other biological barriers to translocate in the human body via the circulatory system. Black carbon (or soot) is a frequent component of PM 2.5 , which exists ubiquitously in the atmosphere. It may be able to invade into the human body through the respiratory system or cross other biological barriers due to their nanoscale size and then accumulate in intracorporeal organs. It has been documented that long-term exposure to black carbon particles may cause a range of health risks, including respiratory diseases, cardiovascular diseases, and neurodevelopmental disorders. Notably, earlier studies have detected black carbon particles in different human organs, including human lung, healthy children urine, and the fetal side of human placenta. Regarding the human brain, some human and animal experiments have suggested that the ambient PM 2.5 species may invade the brain, resulting in the upregulation of inflammatory cytokines and disorder of the central nervous system (CNS). , However, evidence is still insufficient to unravel the exact exposure pathways of PM 2.5 species entering the human brain and their related toxicological mechanisms.…”
Section: Introductionmentioning
confidence: 99%